Kajian Hasil Prediksi Konsentrasi Aerosol PM10 Dari Data ECMWF Dengan Hasil Pengukuran Di Stasiun Pemantau Atmosfer Global Bukit Kototabang (Agam) dan Kota Padang - Darmadi Darmadi (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2021)
Air pollutant emissions originating from forest and land fires as well as from transportation in urban areas are of concern to both stakeholders and the general public. One type of air pollutants that is considered as the main indicator of air pollution is particulate matter 10 micron (PM10). The limited number of locations for measuring PM10 concentrations in the field causes the availability of data and information on air pollutants. This study aims to study the use of data from the ECMWF model as a prediction for PM10 concentration in two locations, namely the Bukit Kototabang Global Atmospheric Monitoring Station and the City of Padang. The research method used refers to quantitative data analysis using correlation methods and descriptive statistics. The results of this study indicate that the concentration of PM10 using ECMWF data on observational data in the city of Padang shows a difference of 25% (H-1), 20% (H-2), and 17% (H-3), and the best predictive value. is for ECMWF data on H-3. Meanwhile, the prediction value of PM10 concentration using ECMWF data on observation data at the Bukit Kototabang Global Atmospheric Monitoring Station shows a value of 12% (H-1), 23% (H-2), and 24% (H-3). The best prediction value for PM10 concentration at the Bukit Kototabang Global Atmospheric Monitoring Station is for ECMWF data on H-1. In general, the PM10 concentration and the observed results show the same profile even though on average the results from the ECMWF provide different concentration values ​​in the two study locations. Keywords: PM10, ECMWF, Bukit Kototabang, Padang City.